Analysis of Probability Distribution Due to Aspiration Level in Fuzzy Matrix Game - Dubey, Sapana P.; Kedar, G. D. (Communications in Mathematics and Applications, 2021)
In this paper, we studied zero-sum matrix game. These games have been represented in form of fuzzy linear programming problems which consists the aspiration level and tolerance level. The aspiration levels are determined on the basis of payoff matrix instead of using probability distribution over the strategies. For a particular tolerance level, the aspiration level is studied and the result are illustrated graphically.
Keywords: Matrix game; Fuzzy Linear programming; Fuzzy membership function